The Pilot Project of the Integrated Border Monitoring System (SISFRON) and the Brazilian state action in the fight against drug trafficking in the State of Mato Grosso do Sul - de Oliveira Alencar, Mylena; Antonio Martelli Contini, Alaerte (Seven Editora, 2023)
This paper seeks to analyze the implementation of the SISFRON Pilot Project and verify the contributions made by the Army’s strategic project in operations to combat transnational crimes on the western border of Brazil, from 2012 to 2021. Starting from a theoretical approach that privileges the regional level of studies on international security the analysis will be epistemologically oriented based on a perspective of international relations, adopting the theory of securitization proposed by the Copenhagen School. Methodologically, this work is intended inductive and is based on a qualitative approach. By applying the theory to the case of drug trafficking on the Brazilian border, the Copenhagen School assigns responsibility to the political and military sectors. The first is a theme that can shake or damage the organizational balance of the State, and the second, by the involvement of the Armed Forces in the issue, being this link to the proof of securitization of the theme. DOI: https://doi.org/10.56238/methofocusinterv1-121